ANALYSIS OF THE COMPLETENESS LEVEL OF EMERGENCY DEPARTMENT MEDICAL RECORDS FOR HYPERTENSIVE PATIENTS AT WANGAYA REGIONAL GENERAL HOSPITAL, DENPASAR - Hijrah Baitu Rahman; Ika Setya Purwanti (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
A complete medical record is a crucial part of healthcare delivery, serving as a communication tool between healthcare professionals, legal evidence, and the basis for evaluating and planning hospital services. The completeness of medical record documentation, particularly in the emergency department, is an indicator of service quality that requires serious attention. The purpose of this study was to determine the percentage of completeness of identification, authentication, recording, and important reporting in the medical records of emergency patients diagnosed with hypertension at Wangaya Regional Hospital, Denpasar City. This study used a quantitative descriptive method. The population was all 330 medical records of emergency patients diagnosed with hypertension. A sample of 199 files was drawn using a probability sampling technique using a simple random sampling approach. The results showed that completeness of identification reached 100%, authentication reached 176 documents (88.44%), recording reached 174 documents (84.44%), and reporting reached 159 documents (79.90%). It can be concluded that identification had the highest level of completeness, while reporting had the lowest level of completeness. Researchers suggest that hospitals increase outreach and supervision of medical staff, especially in emergency installations, regarding the importance of completeness and timeliness of filling out medical record documents.